Deep Coupled Alignment Control for Spacecrafts With Composite Disturbances and Mandatory Pointing Constraint - Teng, Hao; Yang, Yongjian; Qiao, Jianzhong; Zhu, Yukai; Guo, Lei (IEEE transactions on industrial electronics (1982), 2024)
The high-precision alignment of spacecrafts subject to multiple composite disturbances [e.g., axle frictions and back electromotive force (EMF)] and mandatory pointing constraints is an extremely challenging issue for both theoretically and practically. To address this challenge, a refined deep coupled alignment control scheme is proposed in this article. First, a deep coupled alignment model of spacecraft based on the dynamics of the reaction wheel actuator is established, which reveals the influence of the composite disturbances, such as the axle frictions and the back EMF on the system, and separates the composite disturbances into mismatched and matched disturbance according to the affected channels. Second, in view of the characteristics of the composite disturbances, heterogeneous sliding mode disturbance observers (SMDOs) are designed to estimate them accordingly. Then, in order to cope with the mandatory pointing constrains, barrier functions are introduced to convert the alignment errors to limit their variation range. Finally, combined with heterogeneous SMDOs and conversion errors, a composite refined controller is constructed to finely compensate the composite disturbances in the alignment system. High-precision control performance is achieved and the mandatory pointing requirement is satisfied. Simulations and experiments verify the effectiveness of the proposed scheme.